PENGARUH MODAL, PENGALAMAN USAHA, STRATEGI PROMOSI DAN PENDIDIKAN TERHADAP KEUNTUNGAN PELAKU UMKM FASHION PADA MARKETPLACE ONLINE DI KABUPATEN PASURUAN - Aldi, Muhammad Fauzan; Maulana, Adam; Ratnawati, Tri; Hwihanus (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The Industrial Revolution 4.0 has had a major impact on the economic sector. The Internet is one of the factors in technological progress that has caused disruption in the trading sector where trading has shifted from offline to online. This research aims to analyze the effects of capital, business experience, promotional strategies and education on the advantages of SME fashion in online marketplaces in Pasuruan Regency. The population in this study is fashion SMEs in Pasuruan Regency who sell on the online marketplaces Tokopedia, Bukalapak, Shopee, Lazada and Blibli.com with a total sample of 96 respondents taken by accidental sampling and analyzed using multiple linear regression (OLS). The independent variables are capital, business experience, promotional strategies, and education, while the dependent variable in this research is the profits of fashion SMEs. The research results show that the capital variable has a positive and significant effect with a coefficient of 1.80 and a probability value of 0.00, promotion strategies have a positive and significant effect with a coefficient of 77.16 and a probability value of 0.00 and education has a positive and significant effect on profits. fashion UKM practitioners with a coefficient value of 27.3 and a probability value of 0.00. Meanwhile, the business experience variable does not affect the profits of fashion MSME entrepreneurs who sell on online marketplaces.